Human Antimicrobial Peptide Triggered Colloidal Transformations in Bacteria Membrane Lipopolysaccharides. Issue 5 (25th November 2021) - Hong, Linda; Gontsarik, Mark; Amenitsch, Heinz; Salentinig, Stefan
Abstract: Growing concerns of bacterial resistance against conventional antibiotics shifts the research focus toward antimicrobial peptide (AMP)‐based materials. Most AMPs kill gram‐negative bacteria by destroying their inner membrane, but have to first pass the outer membrane covered with lipopolysaccharides (LPS). Their interplay with the LPS is crucial for bactericidal activity, but is yet to be elucidated in detail. In this study, self‐assemblies of Escherichia coli LPS with the human cathelicidin AMP LL‐37, free and encapsulated into glyceryl monooleate (GMO) lipid nanoparticles, are analyzed using synchrotron small angle X‐ray scattering, dynamic light scattering, and cryogenic transmission electron microscopy. Circular dichroism spectroscopy is used to study modifications in LL‐37's secondary structure. LPS is found to form elongated micelles and the addition of LL‐37 induces their transformation to multilamellar structures. LPS' addition to GMO cubosomes triggers the swelling of the internal cubic structure, while in multilamellar GMO/LL‐37 nanocarriers it causes transitions into unstructured particles. The insights on the interactions among LPS and LL‐37, in its free form or encapsulated in GMO dispersions, may guide the design of LPS‐responsive antimicrobial nanocarriers. The findings may further assist the formulation of antimicrobial nanomaterials with enhanced penetration of LPS layers for improved destruction of bacterial membranes. Abstract : Lipopolysaccharides (LPS) can integrate into self‐assembled lipid‐based nanocarriers. The LPS‐triggered colloidal transitions in the nanocarriers can be exploited for targeted delivery of antimicrobial peptides to bacteria.